STRATEGI PEMASARAN HOME INDUSTRY PENGRAJIN ANYAMAN BAMBU DI DESA GINTANGAN KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI - Lilik Sunarsih; Umar HMS (Economic Education, University of Jember, 2015)
Marketing strategy is an overall plan to achieve the goals set. This research aimed to describe the marketing strategy undertaken by bamboo craftsmen in Gintangan Village. The research used qualitative approach with descriptive research design. The research location was determined by using purposive method conducted in woven bamboo home industry of Gintangan Village, District of Rogojampi, Banyuwangi Regency. The research was conducted in four stages: observation, data reduction, data presentation, and conclusion. Based on the research results, it was found that the woven bamboo home industry in Gintangan Village is one of the businesses engaged in the field of woven bamboo handicrafts by applying several marketing strategies in the business activities. The marketing strategies used by home industry included: product development strategy, pricing, marketing place, and promotion.